Gaining an Insight into the User Experience by Becoming a User. (December 2022) - Bennett, Greg
Abstract: In this article, based on his presentation at the BIALL Annual Conference in July 2022, the author Greg Bennett, a law librarian, discusses the insights he gained by becoming a student of law, and so, a user of a law library.